MISCARRIAGES AND ITS RELATIONSHIP WITH DEPRESSION & QUALITY OF LIFE: A COMPARATIVE STUDY - Parvasha Memon; soomro, lubna; Muniza Malik; Saira Almas (Journal of University Medical & Dental College, 2020)
ABSTRACT BACKGROUND & OBJECTIVE: Quality of life describes the way of perception of an individual’s position in life. The objective of this study was to assess the impact of miscarriages on quality of life and depression in women with or without miscarriages. METHODOLOGY: Descriptive Cross sectional study was conducted at different hospitals of Hyderabad, Sindh in six months among 200 participants (100 without miscarriage & 100 with miscarriages). The age range of the participants was 18–40 years. Demographic information was taken to get information about the participants like age, family system, education. Two validated, structured questionnaire namely; Quality of Life (QOL) and Beck Depression Inventory (BDI) were administered. Data was analyzed by SPSS version 23.0, independent sample t-test was applied to observe difference of depression and quality of life among women with or without miscarriages. RESULTS: In the sample among women with miscarriages 42 % were in the age range of 18-30 years and 58 % were of age 31-40 years. Among females without miscarriages 63% were aged 18-30 years and 37% were 31-40 years. Females without miscarriages have education up to masters (20%) and graduation (23%) and most females with miscarriages have primary education (38%). The independent sample mean differences revealed females with miscarriages more depressive (t = 24.407, p<0.05) than females without miscarriages (women without miscarriage =27.52±5.43; women with miscarriage =8.08±5.82). Females with miscarriages feel hopeless 73.3%, guilty 70.3%, highly self-blaming 68.3, and have feeling of complete failure 88.1%. 98% females reported that they don’t cry even they want to, on the other hand only 3% females without miscarriages reported this feeling. The perceived quality of life is higher in women without miscarriages (t =11.75, p= .000), 58.1% females with miscarriages have emotional problems, feeling nervous 59.4% and lack of cheerfulness 63.8%. CONCLUSION: Depression is increasing rapidly in the women that loss their fetus. They feel high sadness, grief and low quality of life as compared to women without miscarriages.